How moonlight shapes environments, life histories, and ecological interactions on coral reefs. Issue 1 (14th March 2022) - Shima, Jeffrey S.; Osenberg, Craig W.; Alonzo, Suzanne H.; Noonburg, Erik G.; Swearer, Stephen E.
Abstract : The lunar cycle drives variation in nocturnal brightness. For the epipelagic larvae of coral reef organisms, nocturnal illumination may have widespread and underappreciated consequences. At sea, the onset of darkness coincides with an influx of mesopelagic organisms to shallow water (i.e. 'diel vertical migrants') that include predators (e.g. lanternfishes) and prey (zooplankton) of zooplanktivorous coral reef larvae. Moonlight generally suppresses this influx, but lunar periodicity in the timing and intensity of nocturnal brightness may affect vertically migrating predators and prey differently. A major turnover of species occurs at sunset on the reef, with diurnal species seeking shelter and nocturnal species emerging to hunt. The hunting ability of nocturnal reef-based predators is aided by the light of the moon. Consequently, variation in nocturnal illumination is likely to shape the timing of reproduction, larval development, and settlement for many coral reef organisms. This synthesis underscores the potential importance of trophic linkages between coral reefs and adjacent pelagic ecosystems, facilitated by the diel migrations of mesopelagic organisms and the ontogenetic migrations of coral reef larvae. Research is needed to better understand the effects of lunar cycles on life-history strategies, and the potentially disruptive effects of light pollution, turbidity, and climate-driven changes to nocturnal cloud cover. These underappreciated threats may alter patterns of nocturnal illumination that have shaped the evolutionary history of many coral reef organisms, with consequences for larval survival and population replenishment that could rival or exceed other effects arising from climate change.